Modelling of color perception of different eye colors using artificial neural networks - (:unkn) unknown (SPRINGER, 2013)
Color is a subjective term that changes according to each person's view. We should define color physically to work with it in terms of printing or any other professional study. However, enabling the observation of color in terms of sales, marketing, product design, and development is as important as product and its packaging. The perception of color and tendencies to colors will be different for people of different eye colors. In this study, different color samples will be shown to five different eye colors of hazel, green, blue, brown, and black eyes both of men and women. The aim of the study is to determine which eye color is more perceived and adopted by which eye color using artificial neural network (ANN) for between 6 and 17 ages. By considering these determinations, it has been studied with graphical and statistical illustrations how different eye color groups prefer colors, how much they are able to recognize primary and secondary colors, and to what extent various eye colors are able to perceive RGB and CMY colors correctly.
Keywords: Color; Color perception; Artificial neural network; THERMODYNAMIC PROPERTIES; SYSTEMS; ALGORITHM